2008
DOI: 10.1007/s00345-008-0276-x
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional ultrasound reconstruction of the pelvicaliceal system: an in-vitro study

Abstract: Three-dimensional ultrasound reconstruction of the porcine PCS is quantitatively comparable to corresponding casts of the PCS. 3D VR movies of the PCS were a fair representation of the PCS anatomy. 3DUS is a potential tool in the planning and execution of percutaneous renal procedures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…In the pioneer study in [23], the authors determined the feasibility and accuracy of 3D US reconstruction of the pelvicaliceal system (PCS) in an in vitro porcine kidney. A further study in [24] has demonstrated that 3D US is more accurate than 2D US for PCS measurements on a customized phantom.…”
Section: Resultsmentioning
confidence: 99%
“…In the pioneer study in [23], the authors determined the feasibility and accuracy of 3D US reconstruction of the pelvicaliceal system (PCS) in an in vitro porcine kidney. A further study in [24] has demonstrated that 3D US is more accurate than 2D US for PCS measurements on a customized phantom.…”
Section: Resultsmentioning
confidence: 99%
“…[37][38][39] Reconstruction of the pelvicalyceal system from 3D US images has been shown to be feasible and anatomically comparable to casts of the collecting system. 40 This may ultimately help optimize stone treatment outcomes.…”
Section: Future Directions In Stone Imagingmentioning
confidence: 99%
“…20 The accuracy of the 4D USG has been evaluated during renal puncture on experimental studies; it provides good quality punctures, such as 2D USG, but improvements in the technology should be expected. [21][22][23] The main advantages of USG are that it is portable, radiation free, cheap, and that radiolucent stones are also visible. The disadvantages are that there is a limited accuracy for renal stones and poor anatomic detail.…”
Section: Ultrasonography (Usg)mentioning
confidence: 99%